ANALISIS PENETAPAN FORMASI JABATAN PPAT DIKABUPATEN TANGGAMUS - Sumarja, Fx (FIAT JUSTISIA)
This study aims to determine the determination of position formations Land Deed Officer (PPAT) in Tanggamus and factors penghambat- his. Determination of position formations PPAT in Tanggamus yet by 3 (three) factors according Permeneg formulation Agrarian / BPN No. 4 of 1999 on the Implementation of the Provisions of Government Regulation No. 37 of 1998 on Regulation of Land Deed Officer Position. In determining the amount of formation of PPAT in a district / city to be seen from the number of districts, the number of registrations and the number of registration of transfer of rights encumbrance. One inhibiting factor in determining formation PPAT positions in Tanggamus is the absence of new rules regarding the determination of the formation of PPATKeywords: Analysis Determination Position Formation P PPAT